ACCOUNTING INFORMATION IN THE FAMA AND FRENCH THREE-FACTORS MODEL - Pondaag, Rianty Nikita Lotazia; Ekawati, Erni (Jurnal Akuntansi dan Keuangan Indonesia, 2020)
The purpose of this study is to reexamine the ability of the Fama-French Three Risk Factor Model to explain stock portfolio returns in countries with different economic levels, as well as examine the effect of accounting information derived from book-to-market on stock portfolio returns. The sample used was a manufacturing company on the Indonesia Stock Exchange and the Tokyo Stock Exchange from 2013-2018. The results show that the three risk factors of the Fama-French model apply consistently to explain the variation in stock portfolio returns in developed markets. For the portfolio of shares in the emerging market, model Fama-French does not consistently assess stock portfolio returns. This research also provides empirical evidence that accounting information contained in book-to-market risk factors is only retained earnings, which has a contribution to the valuation of stock portfolio returns. The results of this study indicate that investors in developed markets are more rational and knowledgeable than emerging markets.